2020
DOI: 10.3390/brainsci10020106
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Removal of Ovarian Hormones on Cholinergic Muscarinic Receptors: Examining Prepulse Inhibition and Receptor Binding

Abstract: Ovarian hormones, such as estrogens and progesterone, are known to exert beneficial effects on cognition and some psychiatric disorders. The basis of these effects is not fully understood, but may involve altered cholinergic neurotransmission. This study aimed to investigate how a lack of ovarian hormones would impact muscarinic receptor-induced deficits in prepulse inhibition (PPI) and muscarinic receptor density in several brain regions. Adult female rats were either ovariectomized, to remove the source of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…It was reported that muscarinic receptor antagonists disrupted PPI (Ch'ng et al, 2020). Jones et al reported that the muscarinic acetylcholine M 1 /M 4 receptor agonist xanomeline improved apomorphine-induced PPI disruption in rats and suggested an interaction between cholinergic and dopaminergic systems in the regulation of PPI.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that muscarinic receptor antagonists disrupted PPI (Ch'ng et al, 2020). Jones et al reported that the muscarinic acetylcholine M 1 /M 4 receptor agonist xanomeline improved apomorphine-induced PPI disruption in rats and suggested an interaction between cholinergic and dopaminergic systems in the regulation of PPI.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies in ovariectomized rats suggested that estrogen level affects mAChRs expression in the cerebral cortex [64], medial basal hypothalamus [67,68], and hippocampus [69][70][71]. Interestingly, a recent study did not find any changes in the density of mAChRs in the brain of ovariectomized rats [72].…”
Section: Genomic Effects Of Steroids On Machrs In Cnsmentioning
confidence: 96%
“…Studies employing receptor-specific antibodies, in situ hybridisation, and tomographic imaging revealed a region-specific negative correlation between muscarinic receptor availability and symptoms of schizophrenia [ 40 , 41 ]. Notably, scopolamine (non-selective muscarinic receptor antagonist) induces psychotic-like symptoms, referred to as "anti-muscarinic syndrome" [ 42 , 43 ]. Based on available evidence from tomographic imaging and post mortem studies, it was proposed that combined agonism of M 1 and M 4 receptors may be more efficacious given that a subgroup of people with schizophrenia also showed M 1 muscarinic receptor deficiency, known as muscarinic receptor deficit schizophrenia (MRDS) [ 44 ].…”
Section: Introductionmentioning
confidence: 99%